Hepatic fat accumulation and regulation of FAT/CD36: an effect of hepatic irradiation - Martius, Gesa (e-Century Publishing Corporation, 2014)
Irradiation is known to induce inflammation and affect fat metabolic pathways. The current study investigates hepatic fat accumulation and fatty acid transportation in a rat model of single dose liver irradiation (25-Gy). Rat livers were selectively irradiated in-vivo (25-Gy), sham-irradiated rats served as controls. Hepatic lipids were studied by colorimetric assays in liver and serum. Intracellular lipids, protein and mRNA were studied by Nile red staining, immunohistology, Western Blot analysis and RT-PCR in liver, respectively. Changes in FAT/CD36 expression were studied in-vitro in a human monocyte cell line U937 after irradiation in presence or absence of infliximab (IFX). Nile Red staining of liver cryosections showed a quick (12-48 h) increase in fat droplets. Accordingly, hepatic triglycerides (TG) and free fatty acids (FFA) were elevated. An early increase (3-6 h) in the serum level of HDL-C, TG and cholesterol was measured after single dose irradiation followed by a decrease thereafter. Furthermore, expression of the fat transporter protein FAT/CD36 was increased, immunohistochemistry revealed basolateral and cytoplasmic expression in hepatocytes. Moreover, apolipoprotein-B100, -C3 and enzymes (acetyl-CoA carboxylase, lipoprotein-lipase, carnitine-palmitoyltransferase, malonyl-CoA-decarboxylase) involved in fat metabolism were induced at 12-24 h. Early activation of the NFkβ pathway (IκBα) by TNF-α was seen, followed by a significant elevation of serum markers for liver damage (AST and GLDH). TNF-α blockage by anti-TNF-α in cell culture (U937) prevented the increase of FAT/CD36 caused by irradiation. Selective liver irradiation is a model for rapid induction of steatosis hepatis and fat accumulation could be triggered by irradiation-induced inflammatory mediators (e.g. TNF-α).